Comparative Performance Analysis of PID and Fuzzy Logic Controllers for AC Motor Speed Control under Load - Sumantri Kurniawan Risandriya; Muhamad Revi Ilhami; Muhamad Ikhsan Azri (Journal of Applied Electrical Engineering, 2026)
The cutting quality of materials such as acrylic and PCB is strongly influenced by spindle speed stability. Excessive speed in acrylic cutting can cause melting and poor surface finish, while low speed increases cutting force and produces burrs. In FR-4 PCB materials, unstable rotation may lead to defects such as delamination and reduced hole quality. Therefore, precise and stable AC motor speed control is essential. This study analyzes and compares the performance of PID and Fuzzy Logic Controllers (FLC) in controlling AC motor speed using a VFD and Arduino in a closed-loop system. Performance is evaluated based on overshoot, rise time, and steady-state ripple error (SSRE) under different setpoints and loads, including 3 mm acrylic and single-layer PCB. Results show that higher setpoints improve stability. The PID controller consistently provides lower overshoot, faster response, and smaller SSRE, especially at low speeds. Overall, PID is more effective, while FLC gives smoother response.